BEZERRA, Nielson Rosa; ROCHA, Elaine (Org.). Another Black Like Me: the construction of identities and solidarity in the African diaspora. Newcastle upon Tyne, UK: Cambridge Scholars Publishing, 2015. 230 p. - CAVALHEIRO, DANIELA CARVALHO (Outros Tempos: Pesquisa em Foco - História, 2015)
IDENTIDADES EM QUESTÃO: escravidão, liberdade e pertencimento no mundo atlântico THE MATTER OF IDENTITY: slavery, freedom and belonging in the Atlantic world LA IDENTIDAD EN CUESTIONAMIENTO: esclavitud, libertad y pertenencia en el mundo atlântico